The 24-hour woman. - Liew-Chng, Cheryl (Morgan James Publishing : Made available through hoopla, 2015)
Think you can have it all? Think again. Then stop thinking and do something different. In this "always-on" global world with increasing work-life demands and career opportunities, the 24-Hour Woman has the wisdom to know that managing it all does not mean having it all. Rather, it means consciously designing a life of happiness and fulfillment. All women experience STRESS-whether they are working professionals, entrepreneurs, or stay-at-home moms. It's what they do with it that matters. Instead of trying to have and do everything, the 24-Hour Woman masters the art of navigating life successfully by focusing first on the legacy she wants to build. Only then can she live a life most excellent-defined by joy and vibrancy. Written by Cheryl Liew-Chng, award-winning global HR consultant on work-life issues and professional development, The 24-Hour Woman offers wisdom and tools from successful women around the globe. The 24-Hour Woman shares strategies for navigating life by focusing first on legacy. Then it lays out case studies and simple daily changes to help you thrive-starting today-and extending through every 24-hour period you live. You will discover: The myths of the 24-Hour Woman and how to get ahead of them; The five Foundational Pillars that every woman must build into her life; What a legacy can do to keep you focused and passionate about your day; How to create "growth friends" to nudge you forward; and What a show host, ceramics artist, and corporate CEO have in common. Learn the secrets and strategies of The 24-Hour Woman-and discover how to thrive in all areas of life. The clock is ticking ... what are you waiting for?